2017
DOI: 10.18280/mmc_b.860403
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Solution of Unsteady Viscous Compressible Fluid Flow along a Porous Plate with Induced Magnetic Field

Abstract: The unsteady viscous compressible boundary layer fluid flow past a semi-infinite vertical porous plate surrounded in a porous medium with induced magnetic field has been studied numerically. The governing non-linear coupled partial differential equations have been transformed by using usual transformations. The obtained non-linear dimensionless coupled partial differential equations have been solved numerically. The explicit finite difference method is used as solution technique and MATLAB software is used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…[14] investigated the fluid flow through parallel plates in the presence of Hall current with inclined magnetic field in a rotating system. Recently the comparison of the obtained results and the published results has been reported by [15].…”
Section: Introductionmentioning
confidence: 86%
“…[14] investigated the fluid flow through parallel plates in the presence of Hall current with inclined magnetic field in a rotating system. Recently the comparison of the obtained results and the published results has been reported by [15].…”
Section: Introductionmentioning
confidence: 86%
“…Some successful studies within a similar calculation framework can be found in Refs. [26][27][28][29][30][31].…”
Section: Calculation Techniquementioning
confidence: 99%
“…The Lewis number has been found to lead the transfer of microorganisms afar from the surface of the sheet. Islam et al [14] executed numerical counting on the MHD densitydependent flow with the magnetic field induction. Mollah et al [15,16] have researched the MHD in-between flow of Bingham materials through parallel Riga and/or porous plates.…”
Section: Introductionmentioning
confidence: 99%